The Hedgehog pathway as targetable vulnerability with 5-azacytidine in myelodysplastic syndrome and acute myeloid leukemia. Issue 1 (December 2015) - Tibes, Raoul; Al-Kali, Aref; Oliver, Gavin; Delman, Devora; Hansen, Nanna; Bhagavatula, Keerthi; Mohan, Jayaram; Rakhshan, Fariborz; Wood, Thomas; Foran, James; Mesa, Ruben; Bogenberger, James
Abstract Background Therapy and outcome for elderly acute myeloid leukemia (AML) patients has not improved for many years. Similarly, there remains a clinical need to improve response rates in advanced myelodysplastic syndrome (MDS) patients treated with hypomethylating agents, and few combination regimens have shown clinical benefit. We conducted a 5-azacytidine (5-Aza) RNA-interference (RNAi) sensitizer screen to identify gene targets within the commonly deleted regions (CDRs) of chromosomes 5 and 7, whose silencing enhances the activity of 5-Aza. Methods and results An RNAi silencing screen of 270 genes from the CDRs of chromosomes 5 and 7 was performed in combination with 5-Aza treatment in four AML cell lines (TF-1, THP-1, MDS-L, and HEL). Several genes within the hedgehog pathway (HhP), specificallySHH, SMO, andGLI3, were identified as 5-Aza sensitizing hits. The smoothened (SMO) inhibitors LDE225 (erismodegib) and GDC0449 (vismodegib) showed moderate single-agent activity in AML cell lines. Further studies with erismodegib in combination with 5-Aza demonstrated synergistic activity with combination index (CI) values of 0.48 to 0.71 in seven AML lines. Clonogenic growth of primary patient samples was inhibited to a greater extent in the combination than with single-agent erismodegib or 5-Aza in 55 % (6 of 11) primary patient samples examined. There was no association of the 5-Aza/erismodegib sensitization potential to clinical-cytogenetic features or common myeloid mutations. Activation of the HhP, as determined by greater expression of HhP-related genes, showed less responsiveness to single-agent SMO inhibition, while synergy between both agents was similar regardless of HhP gene expression. In vitro experiments suggested that concurrent dosing showed stronger synergy than sequential dosing. Conclusions Inhibition of the HhP with SMO inhibitors in combination with the hypomethylating agent 5-Aza demonstrates synergy in vitro and inhibits long-term repopulation capacity ex vivo in AML and MDS. A clinical trial combining 5-Aza with LDE225 (erismodegib) in MDS and AML is ongoing based on these results as well as additional publications suggesting a role for HhP signaling in myeloid disease.